Multicomponent Synthesis of Chiral Bidentate Unsymmetrical Unsaturated N‐Heterocyclic Carbenes: Copper‐Catalyzed Asymmetric CC Bond Formation. Issue 3 (24th November 2014) - Jahier‐Diallo, Claire; Morin, Marie S. T.; Queval, Pierre; Rouen, Mathieu; Artur, Isabelle; Querard, Pierre; Toupet, Loic; Crévisy, Christophe; Baslé, Olivier; Mauduit, Marc
Abstract A multicomponent strategy was applied to the synthesis of chiral bidentate unsaturated hydroxyalkyl‐ and carboxyalkyl‐N‐heterocyclic carbene (NHC) precursors. The newly developed low‐cost chiral ligands derived from amino alcohols and amino acids were evaluated in copper‐catalyzed asymmetric conjugated addition and asymmetric allylic alkylation, which afforded the desired tertiary and quaternary carbon stereocenters with excellent regio‐ and enantioselectivities (up to 99:1 e.r.).